Discrimination and racism in times of coronavirus: The discourse on the social inequality of 'pituqueria' in Peru - Lovón Cueva, Marco Antonio (2022)
There is no population or country in the world that has not been affected by COVID-19, so, as a measure to contain contagions, countries decided to establish partial or total quarantines. In Peru, as of March 16, 2020, and for more than 100 days, citizens had to comply with a mandatory social isolation. Police, military and health personnel were the only ones allowed to move around in order to safeguard lives. Domestic services, food preparation and commerce in general were stopped. In the context of the pandemic, some citizens discriminated and racialized others for not being considered of the same social status. In the case of domestic workers, with a "bed-in" regime, for going to see their families, and, in the case of policemen, for enforcing the rule, they were mistreated by better positioned social sectors. The aim of this paper is to analyze the discourses of discrimination and racialization in times of coronavirus in Peru, generated by what is known in the country as pituquería, that is, by the Peruvian social elite, especially in Lima. To achieve the purpose of the study, two discourses have been chosen that make explicit social practices of racism: the writing 'How to pass the quarantine' in the After party newspaper column by the writer and former Peruvian ambassador to Argentina Maki Miró Quesada, and the verbal aggressions of 'cholification' made by the businessman and lawyer Carlos Wiesse Aserjo. For the analysis of the data, we resorted to the methodological strategies of Critical Discourse Analysis (CDA). The article concludes that the quarantine makes visible asymmetrical ideologies of thinking towards the Peruvian population from the power.